Baboon vaginal microbial flora. Issue 3 (20th May 2016) - Obiero, Jael A.; Waititu, Kenneth K.; Mulei, Isaac; Omar, Farah I.; Jaoko, Walter; Mwethera, Peter G.
Abstract: Background: Knowledge of the composition of vaginal microbial ecosystem is essential for understanding the etiology, prevention, and treatment of vaginal diseases. A baboon model has been used to provide detailed understanding of reproductive physiology and immunology applicable to women. However, little is known about the composition of its vaginal microbial ecosystem. Methods: Gram stain and Nugent scores were used for assessment of baboon vaginal microbial flora. Biochemical identification and analysis of isolates were performed using theapi ® kits and identification software. Results: Species of Lactobacilli, Staphylococci, Clostridia, Bacilli, Corynebacteria, Gram‐negative rods, other Gram‐positive rods, cocci and Candida, were isolated. Healthy vaginal microbiota consisted mainly of lactobacillus morphotypes. Animals with high Nugent scores had increased number of Gram‐positive cocci and variable rods, with increased number of Gram‐negative morphotypes. Conclusions: The baboon vaginal microbiota is heterogeneous in terms of species composition and is typified by a scarcity of lactobacilli.